1985
DOI: 10.1002/chin.198514008
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: PHOTOELECTROCHEMICAL STUDY OF TIN DISULFIDE IN AQUEOUS SOLUTION

Abstract: Unter Bestrahlung (Ä = 480 nm) ist P‐dotiertes SnS2 unstabil gegen saure und basische Medien und die photoelektrochemische Reaktion führt zur Zersetzung des Halbleiters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1985
1985
1985
1985

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The negative shift depends on the concentration of I3-. The shift has been considered to be due to I3-adsorption (2)(3)(4)(5). Photopotentials (Table I) are small and do not vary with redox couples' potential as theoretically predicted.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…The negative shift depends on the concentration of I3-. The shift has been considered to be due to I3-adsorption (2)(3)(4)(5). Photopotentials (Table I) are small and do not vary with redox couples' potential as theoretically predicted.…”
Section: Resultsmentioning
confidence: 92%
“…The corrosion product which stays back on the surface was also dissolved in KOH and the analysis indicated that it was constituted of a mixture of selenium, sulfur, and tin. It seems that .in alkaline medium, hydroxide ions react with the semiconductor in such a way that selenium and sulfur are substituted by these ions in a reaction such as SnSSe + 4 OH---~ Sn(OH)4 + S = + S~ [1] From the fact that the corrosion reaction is accompanied with an anodic current, it is reasonable to assume that a part of S = and Se = formed according to reaction [1] whose energies are sufficiently high can inject electrons into the conduction band and a part diffuse out into the solution according to the following reactions S = ---, S -+ 2e-S-+ H20 ---> SH-+ OH- [2] Se-~Se+ 2e-Se = +H20~SeH-+ OHOn the other hand, thermodynamic consideration indicates that Sn(OH)~ dissolves partly to SnO:~ = in alkaline medium (8) 2Sn(OH)4 ~ SnO3-+ SnO2 + 3H~O + 2H ~ [3] The presence of sulfur, selenium, and tin, both in the solution and in the layer which deposits on the surface, and the fact that the total charge consumed during the electrolysis is six times smaller than the concentration of dissolved tin, would support this interpretation. The addition of Fe(CN)63-to the alkaline solution increases the anodic current and the corrosion rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation